Manufacture of Modified Children's Clothing with Shantung and Cotton Fabrics - Rina Purwanti; Prajna Paramita (Formosa Journal of Social Sciences (FJSS), 2022)
This study aims to determine the process of making children's clothing from cotton and shantung, starting from making the clothing design, measuring the model's body, making patterns and breaking patterns to sewing techniques. It is hoped that the specifications of the product that have been made are that the clothing model is made comfortable and a little loose by applying a collar, sleeveless tops on tops are also modified using shantung materials for variation and mixed and matched with trousers. The materials used are plain cotton with modified shantung motifs. The type of research used is descriptive using a qualitative approach, the focus group discussion method is used to analyze clothing models and the application of fabrics in the manufacture of casual children's clothing. The Focus Group Discussion (FGD) team is a team of panelists who carry out the discussion process during data collection